1997
DOI: 10.1177/08959374970110020901
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Measures and Treatment Needs

Abstract: Clinically evaluated oral health outcome variables from the ICS-II USA data set were examined in the diverse ethnic groups, for two adult age cohorts (35-44 and 65-74 years). These measures were derived from epidemiological examinations and include the DMFT components, loss of attachment, and an indicator of treatment need--the ratio of decayed teeth over decayed and filled teeth. The ratio of decayed over decayed and filled teeth was used in multivariate analysis, since this measure represents an area where p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Female gender was another predisposing variable independently associated with edentulism, and the only sociodemographic variable associated with partial tooth loss, confirming previous findings from the literature (33, 35, 36), including a study performed in a representative adult, urban population of south Brazil where female subjects were more likely to have lost teeth than male subjects (23). However, the reasons why female subjects tended to be more likely to have fewer teeth remain to be elucidated (33).…”
Section: Discussionsupporting
confidence: 86%
“…Female gender was another predisposing variable independently associated with edentulism, and the only sociodemographic variable associated with partial tooth loss, confirming previous findings from the literature (33, 35, 36), including a study performed in a representative adult, urban population of south Brazil where female subjects were more likely to have lost teeth than male subjects (23). However, the reasons why female subjects tended to be more likely to have fewer teeth remain to be elucidated (33).…”
Section: Discussionsupporting
confidence: 86%
“…Other measures of evaluated oral health tend to support this finding that the Navajo are relatively better off among ethnic groups aged 35 to 44 years than they are in the 65-to 74-year-old age group, while the reverse is true for Hispanic adults (Marcus et al, 1997). For example, the middle-aged Navajo are ranked second of all racialethnic groups in periodontal status, trailing only the Baltimore White adults, and actually are ranked first with respect to edentulousness, since no Navajo adults (35-44 years old) in the sample were reported to be without any natural teeth.…”
Section: V0l1u2)supporting
confidence: 55%
“…We chose D/D+F because it represents at least one important component of evaluated oral health status, and we have found that the rankings according to other measures of evaluated oral health status for elderly ethnic groups are often quite similar (Marcus et al, 1997). Thus, for almost all of the alternative measures mentioned above, the Navajo and Lakota Native Americans rank lower in oral health status and exhibit greater treatment needs.…”
Section: V0l1u2)mentioning
confidence: 91%
“…For example, among individuals aged 65 and over, the national adult survey found that over 40% of all seniors were edentulous (Public Heath Service, 1987). Among adults in this study, edentulism was also quite high for the 65-to 74-year-olds (Marcus et al, 1997). Thus, it is interesting to see that, basically, age was not a significant predictor of perceived oral health in two discontinuous age groups.…”
Section: Discussionmentioning
confidence: 88%